Sistem Pendukung Keputusan Dalam Pemilihan Superisor Di Cafe Coup D’Etat J.City Menerapkan Metode ARAS - Muhammad Syahputra (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Supervisor is a company structure that has authority to give instructions to subordinate employees under the direction of superiors. Companies that want to achieve these benefits must improve the individual performance of their employees, because basically individual performance affects the performance of the team or work group, which in turn affects the overall performance of the company. If the company’s performance can be regulated then all aspects of the company can run well, such as the contribution of prospective supervisors to the company more and there is no special method used in evaluating prospective supervisors so that it is not appropriate in the assessment. Decision Support System (DSS) is a computer-based system that creates various alternative decisions to help management solve semi-structured problems using the Additive Ratio Assessment (ARAS) method. Making the right decisions so that the supervisor selection process at Coup D'Etat cafe is in accordance with the required criteria including Age, Education Level, Personality, Expertise and Work Period. From the results of the highest ranking level of alternatives, where the value of each alternative is divided by A0 so as to produce a utility that will be used as a ranking level with the highest value chosen, it can be concluded that the selection of supervisors at Cafe Coup D'Etat must meet the criteria specified above. and get the highest score, then the candidates for supervisor at the cafe are alternatives A7 and A10, namely May Ariska Nst and Otniel Sihombing with values of 0.0681 and 0.0671 respectively.